Does Increasing Mobile Device Coverage Reduce Heterogeneity in Completing Web Surveys on Smartphones?. (June 2019) - Gummer, Tobias; Quoß, Franziska; Roßmann, Joss
Mobile coverage recently has reached an all-time high, and in most countries, high-speed Internet connections are widely available. Due to technological development, smartphones and tablets have become increasingly popular. Accordingly, we have observed an increasing use of mobile devices to complete web surveys and, hence, survey methodologists have shifted their attention to the challenges that stem from this development. The present study investigated whether the growing use of smartphones has decreased how systematically this choice of device varies between groups of respondents (i.e., how selective smartphone usage for completing web surveys is). We collected a data set of 18, 520 respondents from 18 web surveys that were fielded in Germany between 2012 and 2016. Based on these data, we show that while the use of smartphones to complete web surveys has considerably increased over time, selectivity with respect to using this device has remained stable.